A Potent and Specific CD38 Inhibitor Ameliorates Age-Related Metabolic Dysfunction by Reversing Tissue NAD+ Decline - Tarragó, Mariana G.; Chini, Claudia C.S.; Kanamori, Karina S.; Warner, Gina M.; Caride, Ariel; de Oliveira, Guilherme C.; Rud, Micaela; Samani, Adrienne; Hein, Kyaw Z.; Huang, Runqing; Jurk, Diana; Cho, Dong Seong; et al. (Cell metabolism, 2018)
Aging is characterized by the development of metabolic dysfunction and frailty. Recent studies show that a reduction in nicotinamide adenine dinucleotide (NAD+) is a key factor for the development of age-associated metabolic decline. We recently demonstrated that the NADase CD38 has a central role in age-related NAD+ decline. Here we show that a highly potent and specific thiazoloquin(az)olin(on)e CD38 inhibitor, 78c, reverses age-related NAD+ decline and improves several physiological and metabolic parameters of aging, including glucose tolerance, muscle function, exercise capacity, and cardiac function in mouse models of natural and accelerated aging. The physiological effects of 78c depend on tissue NAD+ levels and were reversed by inhibition of NAD+ synthesis. 78c increased NAD+ levels, resulting in activation of pro-longevity and health span-related factors, including sirtuins, AMPK, and PARPs. Furthermore, in animals treated with 78c we observed inhibition of pathways that negatively affect health span, such as mTOR-S6K and ERK, and attenuation of telomere-associated DNA damage, a marker of cellular aging. Together, our results detail a novel pharmacological strategy for prevention and/or reversal of age-related NAD+ decline and subsequent metabolic dysfunction. [Display omitted] •Highly potent and specific CD38 inhibitor, 78c, prevents age-related NAD+ decline•Treatment of old mice with 78c improved physiological and metabolic parameters•Inhibition of CD38 promotes an increase in NAD+ and its precursors in tissue•78c is a novel NAD+-boosting therapy to prevent age-related NAD+ decline A reduction in nicotinamide adenine dinucleotide (NAD+) is associated with aging. Tarragó et al. show physiological and metabolic improvements of aging in old mice given the small molecule 78c, which inhibits the NADase enzyme CD38. Mechanistically, mTORS6K/ERK and telomere-associated DNA damage pathways mitigate the NAD+ decline.